Smart Textile Electrochemical Capacitive Biosensor for Real-Time Monkeypox Virus Detection - de Lima, Lucas F.; Corsato, Paula C. R.; Beluomini, Maisa A. [UNESP]; Ferreira, André L.; Esterdos Santos, Letícia; Barbosa, Priscilla P.; Simeoni, Camila L.; de Jesus, Marcelo Bispo; Proenca-Modena, José Luiz; Paixão, Thiago R. L. C.; de Araujo, William R. (American Chemical Society (ACS), 2025)
The latest outbreak caused by monkeypox virus (MPXV) has turned into an international public health emergency, underscoring the urgent need for rapid, large-scale, and sensitive diagnostic tests for MPXV. Here, a capacitive biosensor for detecting MPXV was developed using a laser-scribed graphene (LSG) sensor manufactured on synthetic aramid fiber. The aramid-LSG sensor was modified with monoclonal antibodies for detecting MPXV through electrochemical capacitance measurements (Cμ-). The electrochemical detection was performed using a system of two interdigitated electrodes, providing excellent reproducibility and without cross-reactivity in the presence of other poxviruses and nonpoxviruses. Also, the wearable textile biosensor achieved a LOD of 7.5 × 10-1 PFU mL-1 and a LOQ of 2.4 × 100 PFU mL-1, enabling its application in plasma, saliva, and PBS samples (simulating application to human skin containing the virus). Furthermore, cytotoxicity assay studies demonstrated that the device is safe to use, according to the in vitro studies employing 3T3 cell cultures. This approach demonstrates the great potential of the wearable capacitive biosensor, which can be manufactured on a large scale using an environmentally friendly method for the wearable analysis of MPXV on patient skin.
Keywords: capacitive measurements; diagnosis; electrochemical biosensor; laser-scribed graphene; monkeypox sensing; wearable textile biosensor